1994
DOI: 10.1007/bf00315829
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cathepsins B, D, and L in the rat osteoclast by immuno-light and -electron microscopy

Abstract: The localization of cathepsins B, D, and L was studied in rat osteoclasts by immuno-light and -electron microscopy using the avidin-biotin-peroxidase complex (ABC) method. In cryosections prepared for light microscopy, immunoreactivity for cathepsin D was found in numerous vesicles and vacuoles but was not detected along the resorption lacunae of osteoclasts. However, immunoreactivity for cathepsins B and L occurred strongly along the lacunae, and only weak intracellular immunoreactivity was observed in the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…Concerning the subsequent organic matrix degradation, as in osteoclastic bone resorption (Goto et al, 1993(Goto et al, , 1994, lysosomal cysteine proteinase such as cathepsin B was previously immunolocalized in human odontoclasts (Sasaki and Ueno-Matsuda, 1992). In the current obser- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the subsequent organic matrix degradation, as in osteoclastic bone resorption (Goto et al, 1993(Goto et al, , 1994, lysosomal cysteine proteinase such as cathepsin B was previously immunolocalized in human odontoclasts (Sasaki and Ueno-Matsuda, 1992). In the current obser- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Northern analysis of mouse tissues for cathepsin K mRNA. Total RNA was isolated from the following mouse tissues: calvarial bone (lane 1), articular cartilage (2), auricular cartilage (3), nasal cartilage (4), pancreas (5), thymus (6), spleen (7), liver (8), kidney (9), brain (10), testis (11), heart (12), intestine (13), skin (14), lung (15), muscle (16), and eye (17). Denatured RNAs were electrophoresed, transferred by blotting onto the hybridization membrane and hybridized with the pMCatK-I probe (A) and with a probe for 28S rRNA (B).…”
Section: Discussionmentioning
confidence: 99%
“…belong to at least two different gene superfamilies, the matrix metalloproteinases (MMPs) and the cysteine proteases (cathepsins). Previous immunohistochemical and in situ hybridization data have demonstrated expression of cathepsins B, D, E, L, OC-2 [8][9][10] and MMP-9 (92 kDa gelatinase) [11] in osteoclasts. Cathepsins B, D and L, as well as most MMPs, are also produced in a variety of other tissues, whereas recent data suggest that OC-2, a novel cysteine protease, and MMP-9 are predominantly expressed in osteoclasts [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Sannes and colleagues [15] employed MNA substrates for demonstration of dipeptidyl peptidases I and II (DPP-I, DPP-II), and showed DPP-I in osteoblasts, osteocytes, and chondrocytes in proliferating and hypertrophic regions of the growth plate, and DPP-II in osteoblasts, osteocytes, and chondrocytes in the resting zone. In the same experiment, they failed to demonstrate cathepsin B activity in the bone, although it was strongly positive in osteoclasts with other enzyme histochemical [5,20] and immunohistochemical studies [6,9,13,16]. Further, there has been no trial to demonstrate AP-A and DPP-IV activities in the bone.…”
Section: Introductionmentioning
confidence: 98%
“…However, there have been very few papers addressing histochemical localizations of proteases, with the exception of cathepsins B, L and D [5,6,9,13,15,20]. Lipp [10] first reported that aminopeptidase-M (AP-M) activity was present in osteoclasts, osteoblasts and endothelial cells at the vascular invasion in growth plate using Leu-2-naphthylamide as a substrate.…”
Section: Introductionmentioning
confidence: 99%